Peningkatan Pemahaman Konsep Keberagaman Budaya Melalui Model Project Based Learning (PjBL) Berbantuan Media Peta Dan Aplikasi Marbel di Kelas V SDN Labang - Tiflah Habibti; Devi Amalia Fajri; Hikmatul Amalia; Moh. Ruslianto; Rachman Firmansyah (Yayasan Citra Dharma Cindekia, 2026)
This classroom action research aimed to improve students’ understanding of cultural diversity concepts in Indonesia through the implementation of the Project Based Learning (PjBL) model supported by the Marbel Budaya Nusantara application. The study was conducted in two cycles involving fifth-grade students of SDN Labang. The results showed a significant improvement in students’ learning outcomes, as indicated by the increase in learning mastery from 76% in the first cycle to 96.6% in the second cycle. The average score also increased from 85 to 89.3, while the number of students who did not achieve mastery decreased from 7 to 1 student. In addition, students’ activeness, collaboration, and engagement in the learning process improved. These findings indicate that the integration of PjBL with interactive digital learning media provides a meaningful and effective learning experience in enhancing students’ conceptual understanding of cultural diversity. Therefore, this approach can be used as an innovative alternative in elementary education learning.